Bytelearn - cat image with glassesAI tutor

Welcome to Bytelearn!

Let’s check out your problem:

Rewrite the function by completing the square.

{:[f(x)=x^(2)+14 x+8],[f(x)=(x+◻)^(2)+◻]:}

Rewrite the function by completing the square.\newlinef(x)=x2+14x+8 f(x) = x^2 + 14x + 8 \newlinef(x)=(x+)2+ f(x) = (x+\square)^2 + \square

Full solution

Q. Rewrite the function by completing the square.\newlinef(x)=x2+14x+8 f(x) = x^2 + 14x + 8 \newlinef(x)=(x+)2+ f(x) = (x+\square)^2 + \square
  1. Given quadratic function: We start with the given quadratic function:\newlinef(x)=x2+14x+8f(x) = x^2 + 14x + 8\newlineTo complete the square, we need to form a perfect square trinomial from the x2x^2 and xx terms.
  2. Completing the square: First, we identify the coefficient of the x term, which is 1414. We then take half of this coefficient and square it to find the number that we need to add and subtract to complete the square.\newline\left(\frac{1414}{22}\right)^22 = 77^22 = 4949
  3. Adding and subtracting: We add and subtract 4949 inside the function to complete the square:\newlinef(x) = x^22 + 1414x + 4949 - 4949 + 88
  4. Rewriting the function: Now we can rewrite the function by grouping the perfect square trinomial and combining the constants:\newlinef(x) = (x2+14x+49)49+8(x^2 + 14x + 49) - 49 + 8\newlinef(x) = (x+7)241(x + 7)^2 - 41
  5. Final answer: The function is now rewritten in the completed square form:\newlinef(x) = (x + 77)^22 - 4141\newlineThis is the final answer.

More problems from Solve a quadratic equation by completing the square